Re-examining the characteristics of pediatric multiple sclerosis in the era of antibody-associated demyelinating syndromes. (November 2022) - Yılmaz, Ünsal; Gücüyener, Kıvılcım; Yavuz, Merve; Öncel, İbrahim and Canpolat, Mehmet and Saltık, Sema and Ünver, Olcay and Çıtak Kurt, Ayşegül Neşe and Tosun, Ayşe and Yılmaz, Sanem and Özgör, Bilge and Erol, İlknur and Öztoprak, Ülkühan and Elitez, Duygu Aykol and Direk, Meltem Çobanoğulları and Bodur, Muhittin and Teber, Serap and Anlar, Banu and , and Yılmaz, Ünsal and Anlar, Banu and Gücüyener, Kıvılcım and Canpolat, Mehmet and Saltik, Sema and Ünver, Olcay and Çıtak Kurt, Ayşegül Neşe and Tosun, Ayşe and Yılmaz, Sanem and Özgör, Bilge and Erol, İlknur and Öztoprak, Ülkühan and Aykol, Duygu and Direk, Meltem Çobanoğulları and Bodur, Muhittin and Teber, Serap and Yıldız, Edibe Pembegül and Yarar, Coşkun and Kara, Bülent and Haspolat, Şenay and İncecik, Faruk and; uk, Gültekin and; er, Cengiz and; ar, Nihal Olgac and; Hüseyin and; l, İbrahim and Demir, Ercan and Dursun, Büşra Daşlı and Dilek, Tuğçe Damla and Türkdoğan, Dilşad and Yalnızoğlu, Dilek and Akbaş, Salih and Güleç, Ayten and Yılmaz, Deniz and Ayanoğlu, Müge and Kanmaz, Seda and Güngör, Serdal and Öztürk, Gülten and Beşen, Şeyda and Haliloğlu, Göknur and Karaca, Nazlı Balcan and Öztürk, Selcan and Yüksel, Deniz and Gürkaş, Esra and Oktay, Seçil and Serin, Hepsen Mine and Karadağ, Meral and Hakkı Akbeyaz, İsmail and Yiş, Uluç and Polat, Burçin Gönüllü and Okan, Mehmet Sait and Bektaş, Ömer and Orgun, Leman Tekin and Günbey, Ceren and Per, Hüseyin and Gültutan, Pembe and Öztürk, Semra Büyükkorkmaz and Aksoy, Erhan and Akyüz, Gülcan and Tekgül, Hasan and Kürekçi, Fulya and Kurul, A. Semra Hız and Çarman, Kürşat Bora and Alikılıç, Defne and Duman, Özgür and Kömür, Mustafa and Yıldırım, Miraç and Alıcı, Nurettin and Gümüş, Hakan and Polat, Muzaffer and Konuşkan, Bahadır and Güngör, Olcay and Mert, Gülen Gül and Edizer, Selvinaz and Mıhçı, Filiz and Öztürk, Sedef Terzioğlu and Yavuz, Merve and Toker, Rabia Tütüncü and Arslan, Mutluay and Şahin, Sevim and Gencpinar, Pinar and Yıldırım, Elif and Yüksel, Ersin and Ekici, Arzu and Deniz, Adnan and Yayici Köken, Özlem and Okuyaz, Çetin and Süt, Nurşah Yeniay and Atasoy, Ergin and Solmaz, İsmail and Yetkin, Mehmet Fatih and Bilgin, Neslihan and Atasever, Aslı Kübra and Tekin, Hande Gazeteci and Dokurel, İpek and Özçelik, Aysima and Aksoy, Ayşe and Türköz, Ayşe Nur and Cavusoglu, Dilek and Özkan, Mehbare and Tekin, Emine and Şahin, Türkan Uygur and Ünalp, Aycan and Koç, Habibe and Sarıgeçili, Esra and Sarıtaş, Serdar and Ayça, Senem and Kayılıoğlu, Hülya and Şenoğlu, Mine Çiğdem and Kamaşak, Tülay and Asadova, Nargis and Keskin, Filiz and Karaoğlu, Pakize and İpek, Rojan and Acer, Hamit
Abstract: Background: The discovery of anti-myelin oligodendrocyte glycoprotein (MOG)-IgG and anti-aquaporin 4 (AQP4)-IgG and the observation on certain patients previously diagnosed with multiple sclerosis (MS) actually have an antibody-mediated disease mandated re-evaluation of pediatric MS series. Aim: To describe the characteristics of recent pediatric MS cases by age groups and compare with the cohort established before 2015. Method: Data of pediatric MS patients diagnosed between 2015 and 2021 were collected from 44 pediatric neurology centers across Türkiye. Clinical and paraclinical features were compared between patients with disease onset before 12 years (earlier onset) and ≥12 years (later onset) as well as between our current (2015–2021) and previous (<2015) cohorts. Results: A total of 634 children (456 girls) were enrolled, 89 (14%) were of earlier onset. The earlier-onset group had lower female/male ratio, more frequent initial diagnosis of acute disseminated encephalomyelitis (ADEM), more frequent brainstem symptoms, longer interval between the first two attacks, less frequent spinal cord involvement on magnetic resonance imaging (MRI), and lower prevalence of cerebrospinal fluid (CSF)-restricted oligoclonal bands (OCBs). The earlier-onset group was less likely to respond to initial disease-modifying treatments. Compared to our previous cohort, the current series had fewer patients with onset <12 years, initial presentation with ADEM-like features, brainstem or cerebellar symptoms, seizures, and spinal lesions on MRI. The female/male ratio, the frequency of sensorial symptoms, and CSF-restricted OCBs were higher than reported in our previous cohort. Conclusion: Pediatric MS starting before 12 years was less common than reported previously, likely due to exclusion of patients with antibody-mediated diseases. The results underline the importance of antibody testing and indicate pediatric MS may be a more homogeneous disorder and more similar to adult-onset MS than previously thought. Highlights: The incidence of pediatric MS is estimated as 0.68 per 100, 000 children in Turkey. Careful exclusion of MOG-IgG disease and other MS mimics allowed accurate description of pediatric MS in this series. No cases of primary progressive MS were recorded among the 634 pediatric MS patients. Onset before 12 years and ADEM-like presentation were less frequent than previously reported. Pediatric MS appears more homogeneous and more similar to adult-onset MS than previously thought.